Simultaneous improvement of exhaust emissions and fuel consumption by optimization of combustion chamber shape of a diesel engine. (August 2017) - Kim, Sang-kyu; Fukuda, Daisuke; Shimo, Daisuke; Kataoka, Motoshi; Nishida, Keiya
In order to achieve clean exhaust gas emissions and high fuel efficiency in diesel engines, a new combustion chamber concept called "egg-shaped piston bowl" was proposed and its effectiveness was validated by engine experiments using a single-cylinder research engine. Numerical simulations of combustion processes and exhaust gas emissions were carried out on different piston bowl geometries using GTT-CHEM code, which is a three-dimensional computational fluid dynamics code coupled with detailed chemical kinetics. In this code, a combustion model taking account of the auto-ignition process of a non-homogeneous mixture and a detailed phenomenological soot model was incorporated. In the detailed phenomenological soot model, particle inception from polycyclic aromatic hydrocarbons, surface growth/oxidation and particle coagulation processes were considered. In addition, to investigate the soot formation characteristics with different piston bowl geometries, experimental measurements by the two-color method were conducted with a constant-volume vessel under high-temperature and high-pressure conditions. As a result of the engine experiments and the numerical simulations, it was confirmed that simultaneous reduction in exhaust gas emissions and fuel consumption was able to be achieved by the egg-shaped piston bowl concept.